Antifungal Susceptibilities of Cryptococcus neoformans - Archibald, Lennox K. (Centers for Disease Control and Prevention, 2004)
Susceptibility profiles of medically important fungi in less-developed countries remain uncharacterized. We measured the MICs of amphotericin B, 5-flucytosine, fluconazole, itraconazole, and ketoconazole for Cryptococcus neoformans clinical isolates from Thailand, Malawi, and the United States and found no evidence of resistance or MIC profile differences among the countries.